Antiviral therapy for recurrent genital herpes - P R Abakarova; E R Dovletkhanova (IP Berlin A.V., 2014)
Herpes infection is one of the most common viral infections in man and presents a serious medical and social problem. In the Russian Federation, the incidence of genital herpes in 2012 amounted to 16.8 per 100 thousand population. The article deals with questions of clinic, diagnostics and applications of antiviral drug with immunomodulatory effects in the treatment of recurrent genital herpes.